Effect of Partial Replacement of Ordinary Portland Cement with Local Marble Waste Powder on the Workability and Compressive Strength of Concrete (Comprehensive Journal of Science, 2026)
The world is witnessing significant advancements in building materials technologies, particularly in the application of sustainability principles and addressing environmental challenges. These challenges include the increasing volume of construction and demolition waste currently disposed of in landfills, which is not a sustainable solution. One of the most important sustainable building materials technologies is the utilization of construction and demolition waste as a partial replacement for concrete components, resulting in economical green concrete with properties similar to the original product. One such waste material is marble waste, which requires large areas of land for disposal. Despite numerous global studies on this topic, there is limited local awareness regarding its potential use in concrete.This research aims to investigate the replacement of Portland cement with marble powder in standard 30 MPa concrete at percentages of 10%, 20%, and 30%, and to determine the impact on the concrete's fresh and hardened properties through slump and compressive strength tests.The results showed that the 28-day compressive strength is acceptable up to a 10% replacement with marble powder, achieving a compressive strength of 27.3 MPa. Replacing cement with marble powder increases the workability of concrete.Furthermore, replacing cement with a waste construction materials powder significantly reduces costs. Experiments have shown that one to two bags of cement can be reduced per cubic meter of concrete without significantly affecting its properties.
Keywords: Construction waste, marble, green concrete, partial cement replacement, sustainable building materials